Use of Pedagogical Content Knowledge in Teaching Chemistry in Early Science Education - Usak, Muhammet; Ozden, Mustafa; Saglam, Yilmaz (Asian Journal of Chemistry, 2011)
The purpose of this research was to explore the pedagogical content knowledge of prospective primary school teachers on the subject of phase transitions of matter consisting sample of 41 prospective primary school teachers. Content knowledge test, pedagogical knowledge questionnaire and semi-structured interview were used to collect data. This study showed that primary student teachers had various problems related to the phase transitions of matter as well as teaching. The main problems of student teachers were insufficient content knowledge, misconceptions and lack of knowledge about instructional strategies, assessment and evaluation. The results of this study impressed that prospective primary school teachers had different methods of using technology for teaching about the phase transitions of matter. This study proposes some pedagogical implications for teacher education.